COVID-19 in Nigeria: An Analysis of the Early Epidemiological Trend of the Infection and Response Efforts - Olorunda Rotimi; Adesegun O Fatusi (The Proceedings of the Nigerian Academy of Science, 2020)
This paper presents an epidemiological analysis of the trends in Covid-19 infection in the first 100 days of the pandemic in Nigeria and the response efforts in the country. Data from the Nigerian Centre for Disease Control and other relevant sources were analysed toshow the national trend and compare sub-national trends. Analysis revealed that the infection rate is rising in the country despite efforts at lockdown and restriction of movements. Over the 100 days of focus, Nigeria recorded 15,181 cases with a case fatality rate (CFR) of 2.6%. Age 31-40 years had the highest number of cases, while only 8% occurred in individuals over 60 years. All the infections recorded in the first 24 days were in the South-west region. The South-west region had overall highest numberof cases (56.7%) but the lowest CFR rate (1.5%), while South South region had the highest CFR (4.8%). CFR ranged from 0% (5 states) to 17% in Anambra State. Lagos, Federal Capital Territory (FCT) and Kano –the main hubs of international travel into Nigeria –were the epicentres of the infection and recorded 60% of all cases. Three-fifths of the confirmed cases (60%) were concentrated in 20 Local Government Areas (LGA), comprising 2.6% of the country’s 774 LGAs. Nigeria is performing exceptionally low number of tests (<15% of declared national capacity) to diagnose the disease and facilities to perform the test are unevenly distributed. More context driven local actions are needed even as the country thinks and learns from the global experience of the disease